Breast milk additives and infant formula - Sherriff, Jill; McLeod, G. (Springer, 2013)
Breast milk is recommended for very preterm infants but fortification is required to increase its nutrient density in order to promote growth and development. Even with fortification, those born extremely preterm and those who are fluid restricted may not achieve intrauterine growth targets. Thus, fortification beyond routine amounts may be necessary for some infants. Further study is necessary to determine optimal methods, types and amounts of fortification, as well as upper limits of osmolality, so as to ensure avoidance of feeding intolerance and necrotizing enterocolitis whilst achieving appropriate rate of weight gain and accretion of nutrients. The efficacy of new formulations of fortifiers and infant formulae needs further study.